REVIEWS AND OPINIONS OF THE CHINESE SCIENTIST ON THE DEFINITION OF APPLIED LINGUISTICS IN CHINA - Hunko, Liubov (Social work and education, 2018)
The qualified education is a base of the economic development of the country. Under the conditions of the intensive globalization and internationalization, computerization of manufacturing, the rapid development of the latest technologies there is a need for a high quality vocational training of the masters on the foreign language and Applied Linguistics. According to our study one of the main aims is the research about the development of the Applied Linguistics in China, the description of the term Chinese scientists use in their papers. Thus the main aims of the paper are: to present the terms and definitions of Applied Linguistics the Chinese researches use in their studies; the illustration of the peculiarities of Applied Linguistics as a science in China; the description of the tasks the Chinese linguists face with. Scientists engaged in Applied Linguistics in China must simultaneously develop science and at the same time pay attention to the benefits this science brings to society. Linguistics in China is developing in 3 directions: teaching of the Chinese language, the development of the languages of the national minorities and teaching foreign language. There can be distinguished main tasks the linguists in China face with: the development of theoretical problems – starting with a systematic approach; the studying of the patterns of education and use of linguistics; teaching Applied Linguistics in order to increase the level of linguistic preparation of students; the research of the various tools for the compilation of the dictionaries in accordance to the requirements of the society. Today, language policy and linguistic science are the part of the political, economic and social changes, which help to improve the image of China abroad. Foreign (first of all Chinese) and Ukrainian scientists in different ways interpret the concept of Applied Linguistics, and that is why not in the same way outline the scope of the research of this science. Because of the varying ways to outline the subject specificity of Applied Linguistics, resume that it leads to differences in the substantiation of the conceptual, structural, content, organizational and pedagogical principles of the professional training of the masters of foreign languages and Applied Linguistics.